Decolonization of carbapenem-resistant Klebsiella pneumoniae from the intestinal microbiota of model mice by phages targeting two surface structures - Liu, Ju-Yun; Lin, Tzu-Lung; Chiu, Ching-Yu; Hsieh, Pei-Fang; Lin, Yi-Tsung; Lai, Li-Yin; Wang, Jin-Town (Frontiers in Microbiology, 2022)
Background: Klebsiella pneumoniae is a normal component of the human gastrointestinal tract microbiota. However, in some cases, it can cause disease. Over the past 20 years, the prevalence of antibiotic-resistant bacteria, such as carbapenem-resistant K. pneumoniae (CRKP), has been increasing. Methods: We attempted to specifically eliminate CRKP from a mouse model with human intestinal microbiota. To establish humanized microbiota-colonized mice, we administered K64 CRKP-containing human microbiota to germfree mice by faecal microbiota transplantation. Then, we used two phages, one targeting the capsule (phage K64-1) and one targeting O1 lipopolysaccharide (phage KO1-1) of K64 K. pneumoniae, to eliminate CRKP. Results: In untreated control and phage KO1-1-treated K64-colonized mice, no change in CRKP was observed, while in mice treated with phage K64-1, a transient reduction was observed. In half of the mice treated with both phage KO1-1 and phage K64-1, CRKP was undetectable in faeces by PCR and culture for 60 days. However, in the other 50% of the mice, K. pneumoniae were transiently reduced, but recovered at 35 days after treatment. Conclusion: Combination treatment with phage K64-1 and phage KO1-1 achieved long-term decolonization in 52.3% of mice carrying CRKP. Importantly, the composition of the intestinal microbiota was not altered after phage treatment. Therefore, this strategy may be useful not only for eradicating drug-resistant bacterial species from the intestinal microbiota but also for the treatment of other dysbiosis-associated diseases.